Drone remote control warfare - Gusterson, Hugh (The MIT Press, 2016)
In this book, Hugh Gusterson explores the significance of drone warfare from multiple perspectives, drawing on accounts by drone operators, victims of drone attacks, anti-drone activists, human rights activists, international lawyers, journalists, military thinkers, and academic experts.